HIGH-PRESSURE, METASOMATIC ROCKS ALONG THE MOTAGUA FAULT ZONE, GUATEMALA - Harlow, George E.; Sisson, Virginia B.; Avé Lallemant, Hans G.; Sorensen, Sorena S.; Seitz, Russell (Ofioliti, 2003)
The Motagua River of Guatemala follows the Motagua fault zone, the present plate boundary zone between the North American (Maya block) and Caribbean (Chortís block) plates. The central Motagua River valley is bordered by E-W-striking tectonic slices of serpentinite, some of which contain blocks of high pressure/low temperature (high P/T) eclogite, garnet amphibolite, and jadeitite. Recent exploration for commercial jadeitite (jade) has discovered considerable quantities of high P/T rocks in serpentinite bodies both further along and farther from the river. The southern bodies, south of the Motagua fault zone and adjacent to Chortís basement, also contain abundant eclogite, glaucophane eclogite, blueschist, jadeitite, and other high P/T rocks. The northern bodies, adjacent to Maya basement, include abundant jadeitite, albitite, and garnet amphibolite, but rare eclogite. Our initial studies find metasomatic signatures in most of the high-P/T rocks (e.g., phengite and quartz in veins, oscillatory zoning of jadeite and phengite, etc.). Mineralogical differences between jadeitites from the northern and southern bodies, and the different lithotectonic assemblages on the two sides of the Motagua fault zone suggest that either two high P/T events have occurred, or the two belts may be a single unit disrupted by strike slip duplexing.